P022 Autologous hematopoietic stem cell transplantation in refractory Crohn's disease: series case report in a Brazilian tertiary center. (July 2019) - Jane, Oba; Cinthya, Silva; Sandra, Nakashima; Mirele, Santos; Andreza, Ribeiro; Flavio, Steinwurz; Orlando, Ambrogini Junior; Nelson, Hamerschlak
Abstract : BACKGROUND: Crohn's disease (CD) is a chronic inflammatory and relapsing disease that can affect any segment of the gastrointestinal tract causing intestinal and extra-intestinal manifestations. A significant percentage of these patients suffer an aggressive disease course, refractory to pharmacological therapy and most of them are not favorable to surgical treatment, besides not being a curative procedure. Recent analysis of autologous haematopoietic stem cell transplantation (HSCT) showed a high rate of clinical and endoscopic remission after 1 year in these patients. METHODS: In 2015 our hospital developed a partnership protocol with ministry of health to submit adult patients from many cities of Brazil, with refractory CD to perform HSCT as an optional treatment. The follow up period of this protocol was only 6 months. We analyzed the 6 patients from this protocol to assess the efficacy and safety of autologous HSCT for refractory CD. RESULTS: Five men and 1 woman, between 43y and 19y (median age 38y), corporal index mass 20 Kg/m 2 (18–25), with refractory CD, median course of illness 14y (5–23 years), all negative for X-linked inhibitor apoptosis protein (XIAP). Two patients were non-structuring non-penetrating, but only one hadn't had previous surgery. Five patients had 2–3 previous intestinal surgeries, and one had ileostomy, 2 had tuberculosis, one had multiple sclerosis, one had epilepsy and depression and one had pancreatitis as comorbities before HSCT. One patient had reactivation of tuberculosis and was treated during 6 months before the HSCT. All patients used thiopurines, metotrexate and more than one immunobiological therapies (IFX, ADA, VEDO), steroids, antibiotics, and aminosalicylates. All the 6 patients completed the mobilization, conditioning and transplantation phases, during a median time of hospitalization of 35 days (21–58d). We had no transplant related mortality. All patients had infectious complications during mobilization which included febrile neutropenia, anemia and life-threatening complications as KPC, Staphylococcus aureus infecction, and sepsis caused by E. coli . Among non-infectious complications all had mucositis, and red cell transfusion was required in all patient. The 6 months follow up of protocol all patients reached clinical and endoscopic remission and were steroid and immunosuppressive free remission. Most of them related viral infections. Only the youngest patient answered the SF36, IBDQ and PedsQL4.0 questionnaire pre and post HSCT, with improvement of health-related quality of life in all domains. Although the project last 6m, actually all patients are alive and the longest post HSCT time is 2y 9m. Only one patient restarted ADA as monotherapy (1y11m post HSCT). CONCLUSION: Due to its high complexity, risk of infections and death we consider that autologous HSCT should be an option of treatment only for patients with severe refractory CD.